What future for banana-based farming systems in Uganda? A participatory scenario analysis - Ronner, E.; Ven, G.J. van de; Nowakunda, K.; Tugumisirize, J.; Kayiita, J.; Taulya, G.; Uckert, G.; Descheemaeker, Katrien K. (Elsevier, 2023)
CONTEXT Population pressure, land scarcity and encroachment of nature reserves are challenging sustainable intensification of agriculture in Uganda. One of the main staple crops in Uganda is East African Highland banana. Area expansion and improved management have enhanced the economic performance of banana, yet at the expense of food security, environmental and social sustainability. While a transition of banana-based farming systems to a more sustainable future seems necessary, the desired future state and pathways of getting there may differ among actors involved.